ANALYSIS OF STUDENTS DIFFICULTIES IN LEARNING HEREDITY OF XII GRADE STUDENTS IN SMA SWASTA HARAPAN 1 MEDAN ACADEMIC YEAR 2015/2016 - Putri Wita Sari; Fauziyah Harahap (Universitas Negeri Medan, 2016)
This study aims to detect the students difficulties in learning heredity topic and the factors thatinfluence on it. A descriptive research design was used in this study to describe the level of students difficultiesbased on cognitive and learning indicator aspect and also the causing factors. The population are taken fromwhole of XII Grade Students in SMA Swasta Harapan 1 Medan. There were 3 classes chosen as the sample byapplying cluster random sampling technique. The instruments used to obtain data were multiple choice test,essay test, concept map and questionnaire. The result of data analyzed showed : (1) On cognitive aspect, thedifficulties are categorized into very high difficulties from C1 until C6 level of cognitive which the highestpercentage is on C6 category as 80,21%, (2) On learning indicator aspect, the students have very highdifficulties in explaining the causing of pseudo deviation of Mendelian Law as 72,32%, (3) Society is the factorsthat categorized as influential in causing students learning difficulties which is 76,77%.Keywords : learning difficulties, cognitive aspect, learning indicator, heredity